The Influence of the Project Based Learning Model on Learning Outcomes PPKN On Fourth Grade Students - Anggun Anugrah Manurung; Eva Pasaribu; D. Yuliana Sinaga (Journal Of Global Research Publications, 2025)
This  research  aim  For  knowThe  Influence  of  the  Project  Based  Learning  Model  on  Learning Outcomes PPKN On Students of Class IV of UPTD SD Negeri 122350 Pematangsiantar.Research design implementedis  Pre-Experimental  Designs  method  is  appropriate  with  limitations  amount  samples  to  be researched.This research will was held at the UPTD of State Elementary School 122350 Pematangsiantar.The time study implemented in the even semester May of the Year Academic Year 2023/2024. Based on results  research  and  discussion  that  has  been  put  forward  can  taken  conclusion  that  from  pretest  results,obtained the average value is 46.35 which is classified as in category low.While average value of results Study posttest students, namely 85.52, which indicates that results after given treatment increase with such a  range  big.From  the  average  pretest  and  posttest  scores  there  are  difference  of  39.17  and  based  on hypothesis test results with level significant = 0.05 and ttable of 2.034, thitung of 14.737. With thus thitung> ttable 14.737> 2.034, then can concluded that there is the influence of the Project Based Learning Model on results learning PPKN for students  Class IV of UPTD SD Negeri 122350 Pematangsiantar.Maka based  on  Hypothesis  Test  Results   is  rejected  and accepted  which  indicates  that  existence  the influence of the Project Based Learning Model is significant to results learning PPKN for students  Class IV of UPTD SD Negeri 122350 Pematangsiantar.